Energy-Saving Effects of the Intermittent Control of Pumps in Ground Source Variable Refrigerant Flow Systems with a Buffer Water Tank - Toya Tanaka; Sayaka Kindaichi; Keita Kawasaki; Daisaku Nishina (Energies)
Variable refrigerant flow (VRF) systems are common air-conditioning systems used in regions with moderate climates that have cooling and heating demands. Unlike typical air-source VRF systems, ground-source VRF systems require heat-source water circulation, and reducing the pumping power remains a significant problem. Herein, the intermittent pump control for circulating heat source water was achieved by installing a buffer water tank between the ground heat exchangers and VRF units. An intermittent control methodology was developed based on the indices of water transport efficiency and incorporated into a system simulation model with 72 boreholes, a cooling capacity of 252 kW, and a buffer water tank of 30 m3. Results indicated that intermittent control was achieved at heat load ratios lower than 40% as expected. This intermittent control allowed more efficient water transport with 38% lower pumping power than conventional inverter controls. Although the proposed system equipped more pumps and heat exchangers than conventional systems, it exhibited higher energy efficiencies for most measurement days than the conventional air-conditioning systems. The annual energy consumption was thus reduced by 34% and 8% compared to air-source VRF systems and conventional ground-source VRF systems, respectively.